Pengaruh Komitmen Keorganisasian dan Kepuasan Kerja terhadap Kinerja Tenaga Edukatif/ Dosen (Studi di Universitas Brawijaya Malang) - Sudiro, Achmad (Universitas Brawijaya, Indonesia, 2009)
The impact of organizational commitment and job satisfaction toward academic staffs performance (study on Brawijaya University in Malang). The aim of this research is to know the effect of organizational commitment and job satisfaction toward the performance of academic staffs. The study was executed using samples of 100 respondents (lecturers on Brawijaya University at Lector, Head Lector and Professor). The finding of such analysis indicated that the product of R2 was 0,162 or as amount 16,2%. Which mean 16,2% of dependent variable could be explained by the independent variables . On the other hand, the remaining 83,8% was described by other variables that was not included in this study. The result of F test shows that all the independent variables (organizational commitment and job satisfaction) simultaneously affect academic staff performance significantly. In addition, the result of t-test showed that the commitment variable gave significant effect on the academics staffs (lecturers) performance. While the job satisfaction variable give not significant effect on the academic staffs (lecturers) performance.